Food security: concepts and definitions - Norhasmah S,; Zalilah MS,; Asnarulkhadi AS, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Background : The purpose of this article is to review the definitions of food security and food insecurity as well as the concepts related to food security. Methodology: This is a systematic review on a few papers, research, and articles according to studies and research by various organizations, experts, scholars on food security in developed and developing countries. Result : The first definition of food security was given to reflect the comprehensive concerns on the availability of world food supplies. The definition was expanded to incorporate accessibility of food for all people at all times. Then, the complex definitions of food security incorporated food accessibility and availability as well as the quality of food intake. Latest definition integrates the social aspect of food that should be accessed in a socially acceptable way. Broad definition of food insecurity and several terms that closely related were also discovered. The four main concepts of food security from these definitions were identified; availability, accessibility, acceptability and adequacy. These concepts of food security are relevant to micro, meso and macro levels of social and administrative organizations. Conclusion : Understanding definitions and concepts of food security can assist researchers, policy makers and program implementers to conduct research that address the issues of food security.